Ethical aspects of medical informatics: principles for use and appropriate user of computational systems in clinical health care - Suárez-Obando, Fernando; Ordóñez Vásquez, Adriana (Acta Bioethica, 2012)
Medical Informatics (MI) studies the intersection among computer technology, medicine and the influence of electronic clinical history and the intelligent systems for diagnosis support in clinical decision making. The inadequate use of technology may divert the purposes of MI towards an inadequate use by third parties involved in clinical health care, such as health care managers or insurance agents. The principles for “use and appropriate user for MI applications” as base are proposed to manage suitably computational technology in health care. The development of these principles must be based in the evaluation of their applications, emphasizing that the evaluation must be carried out with the same considerations as other types of medical or surgical interventions.